2007
DOI: 10.1111/j.1600-0404.2007.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of glial fibrillary acidic protein correlate to tumour volume of high-grade gliomas

Abstract: Serum levels of GFAP demonstrated a linear correlation to tumour volume in patients with high-grade gliomas. GFAP seems to be a more reliable biomarker in patients with high-grade gliomas than the commercially available S-100B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…Levels of a proliferation-inducing ligand (APRIL) have been found to be elevated in the sera of glioblastoma (GBM) patients when compared to non-tumor controls (3). Another study suggests serum levels of glial fibrillary acidic protein (GFAP) are correlated with tumor volume in high-grade gliomas (4). Recently, insulin-like growth factor binding protein-2 (IGFBF-2), measured in plasma, was shown to be up-regulated in high-grade glioma patients when compared with grade II glioma patients and normal controls, and its expression levels can predict clinical outcomes of patients with highgrade gliomas (5).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of a proliferation-inducing ligand (APRIL) have been found to be elevated in the sera of glioblastoma (GBM) patients when compared to non-tumor controls (3). Another study suggests serum levels of glial fibrillary acidic protein (GFAP) are correlated with tumor volume in high-grade gliomas (4). Recently, insulin-like growth factor binding protein-2 (IGFBF-2), measured in plasma, was shown to be up-regulated in high-grade glioma patients when compared with grade II glioma patients and normal controls, and its expression levels can predict clinical outcomes of patients with highgrade gliomas (5).…”
Section: Introductionmentioning
confidence: 99%
“…Interrelation between serum GFAP concentration and the tumor size in CNS was recently reported [5][6][7]15,16]. These studies stemmed from the fi nding that patients with stage IV glioblastoma had higher level of GFAP in comparison with patients with more differentiated tumors.…”
Section: Resultsmentioning
confidence: 95%
“…Subsequent experiments showed that low-differentiated glioma cells per se do not contain GFAP [5,7,10,14,15]. Despite impressive number of papers examining the relationships between GFAP and morphometric indices of glioblastomas [5,7,8,15,16], there are no published reports on the dependence of serum GFAP on the intensity of astroglial reaction.…”
mentioning
confidence: 97%
See 2 more Smart Citations